Recent advances in stem cell-based therapies for type 1 diabetes: A glimpse into the future - Ahmed Hassanein; Saghir Akhtar (Biomolecules & Biomedicine)
Type 1 diabetes mellitus (T1DM) is a serious, chronic metabolic and autoimmune disease that affects millions globally. While insulin administration remains the most effective treatment, it is not a cure. Long-term therapies, such as immunotherapy, can be effective for some patients, but they have notable limitations and do not provide a permanent solution. As a result, current research has shifted towards stem cell-based therapies, which offer a potentially expandable and scalable source of pancreatic beta cells. These therapies aim to restore long-term endogenous β-cell function in all T1DM patients, provided they can avoid immune recognition and rejection by the host. In this review, we will discuss the latest first-in-human successes of stem cell therapies for T1DM. We will then explore stem cell-derived islet encapsulation technologies and hypoimmune stem cells, examining how they might overcome the need for immunosuppressive therapy. Additionally, we will provide a summary of recent and ongoing biopharmaceutical industry pipelines and clinical trials for stem cell therapies aimed at treating T1DM. These advances suggest that stem cell therapies offer a promising and highly effective approach to treating patients with this chronic disease. However, large-scale clinical trials over the long term are necessary to verify these early successes and assess the curative potential of stem cell therapy for T1DM.